2007
DOI: 10.1136/tc.2007.020362
|View full text |Cite
|
Sign up to set email alerts
|

Smoking too few cigarettes to be at risk? Smokers’ perceptions of risk and risk denial, a French survey

Abstract: Background: Past studies on smokers' risk perception have produced mixed results. We endorsed a new approach to assess smokers' perceptions of risk by asking them to estimate threshold values for the cancer risk associated with daily consumption of tobacco and number of smoking years. We expected that many smokers would endorse a ''risk denial'' attitude, with threshold estimates higher than their own smoking consumption and duration. Methodology: A French national telephone survey (n = 3820; 979 current smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 32 publications
(25 reference statements)
3
43
0
1
Order By: Relevance
“…A French cross-sectional survey reports that smokers with low cigarette consumption tend to endorse selfexempting beliefs that they smoke too few cigarettes to endanger their health [10] . Additionally, a study among light smokers enrolled in a randomized cessation trial has revealed that they smoke mainly for negative affect reduction and stimulation [11] .…”
Section: Introductionmentioning
confidence: 99%
“…A French cross-sectional survey reports that smokers with low cigarette consumption tend to endorse selfexempting beliefs that they smoke too few cigarettes to endanger their health [10] . Additionally, a study among light smokers enrolled in a randomized cessation trial has revealed that they smoke mainly for negative affect reduction and stimulation [11] .…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still myths regarding the individual risk for the development of cancer. (15) A study carried out in France showed that 44% of the smokers believed that smoking might lead to cancer only if tobacco consumption were higher than their own and that 20% of the smokers believed that their cancer risk would be increased only if the number of pack-years were greater than their own. (15) Another factor that is associated with smoking cessation attempts in patients with smoking-related diseases is the motivation that appears when certain diseases are diagnosed.…”
Section: Resultsmentioning
confidence: 99%
“…(15) A study carried out in France showed that 44% of the smokers believed that smoking might lead to cancer only if tobacco consumption were higher than their own and that 20% of the smokers believed that their cancer risk would be increased only if the number of pack-years were greater than their own. (15) Another factor that is associated with smoking cessation attempts in patients with smoking-related diseases is the motivation that appears when certain diseases are diagnosed. (17,18) Patients who are informed about their lung age and about the influence of smoking on the evolution of airway obstruction show a higher smoking cessation rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certaines croyances propices au déni du risque tabagique s'avèrent largement répandues [14], même parmi les nonfumeurs. Les deux tiers des Français pensent ainsi que respirer l'air des villes est aussi mauvais pour la santé que de fumer des cigarettes, que l'on peut fumer toute sa vie sans jamais être malade, ou qu'un fumeur peut éviter les effets nocifs du tabac s'il s'arrête à temps.…”
Section: Discussionunclassified